(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article is about the origins of religious radicalism. The author examines in detail the exogenous factor in the development of Islam in Kazakhstan. As a result of external influence, «new Muslims» phenomenon appeared, for whom belonging to the global Muslim community turned out to be more significant than belonging to its ethnic or national group. Thus, there was an important shift in the status of Islam in Kazakhstan’s society — Islam occupied its place in society as a religious ideology. In turn, the new Islamic Ummah denies traditional ethnocultural and religious values, does not recognize secular government, which leads to the problems of their integration into Kazakhstani society. Strict secular policy complicates the situation in society which promotes social exclusion of believers, who practice non-traditional Islam, strengthen their views on the hostility of the state to religion, and, therefore, their transition to the opposition camp. Key words: religious radicalism, Islamism, Islamic revival, re-Islamization.